FILOSOFI KEPRIBADIAN DAN KEPEMIMPINAN DALAM MEMBENTUK BUDAYA KERJA ORGANISASI - Abdul Wahid Mahsuni; Sutrisman, Dede Yusuf; Fathul Bachri; Shofi Mustajibullah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstract Leadership not only involves the ability to influence and motivate others but also reflects the philosophy and principles upheld by a leader. The purpose of this research is to examine contemporary theories and case studies on how leadership philosophy can shape an inclusive, innovative, and adaptive work culture. This study employs a literature review method by utilizing various references related to leadership philosophy. The conclusion drawn is the influence of transformational leadership philosophy in building an inclusive and adaptive work culture in modern organizations. In its implementation, this philosophy is applied through employee empowerment, strengthening collaboration, and fostering innovation, which ultimately creates a productive work environment that is relevant to the ever-evolving market needs. Keywords: Leadership, Personality, Leadership Philosophy